(untitled) (Journal of Laboratory Animal Science, 2022)
BALB/c strain is the most commonly used animal research mouse model in biology/Bio-medical research. From BALB/c strain many of inbred, congenic and transgenic models were established and being used for the betterment of humans as well as domestic animals. At CSIR-IIIM, Jammu animal house facility conducted study for evaluation genetic diversity of inbred lines of BALB/c strain. Animals were maintained in SPF condition with routine health monitoring. Selection was conducted based on growth and reproduction performance of the mothers. Four selected lines and an unselected control line were maintained throughout the experiment. After, 20th generation of full sib mating, we obtained three different lines. All the three lines of BALB/c strain shows standardized litter size of 8 pups at birth. All line mice were genotyped by using established 14 pair of microsatellite markers and genetic diversity analysis. The Effective number of alleles was reported 1.021±0.016 in overall experimental population. Shannon’s Index for within lines was 0 and among lines was 0.019±0.014. The Estimated Diversity (u) was 0 for within lines, 0.052 ±0.036 for control lines and 0.013±0.009 for among population. Polymorphic information content (PIC) observed in D11Mit260 marker. Line1 was showing very little Genetic distance with Line 2 (0.154) followed by control line (0.114) and Line 3 (0.074). Control line and Line 2 showed very close genetic distance (0.010). It is concluded that BALB/c strain has no diversity within line and has very little diversity between lines after 20th generation of full-sib mating.